Principles and practice of local government in Nigeria - Umoren, Ezekiel E. (Jos, Nigeria : Fab Education Books, 1994)
This volume provides details on the earlier developments of local government administration in Nigeria including procedure and resources for development as well as the challenges.
Includes bibliographical references (p. 243-246) and index.
lje 22/1/19
Loans
Keywords: Local government; Nigeria